TEACHERS’ INFLUENCE ON STUDENTS IN THEIR LIFELONG DEVELOPMENT - Malureanu, Flavia; Enachi-Vasluianu, Luiza (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The impact teachers have on their students is imprinted to a much extent in each person’s life. Every child, teenager or adult speaks of present or previous experiences related to teachers who left their marks on their development in life. Teachers are important people in children’s life providing them with education, discipline, motivation and role-models. The guiding role of teachers is not limited to school classroom and school disciplines, but it surpasses didactic activities and extends into personal life. Truth is that children feel differently the influence exerted by teachers due to their sensitivity, personalities, life experiences. The identification of the aspects that influence students to a greater or less extent is important as it helps to shape a profile of an authentic teacher as s/he is perceived by students. Such a perspective may help teachers become aware of their role in students’ lives and as a consequence they should make adjustments in order to become better partners for their students.The present paper intends to study teachers’ impact on students in their life lifelong development. The aspects taken into consideration, according to specific literature and experiences in classrooms, were: school performances, behavioural patterns, adjustment to school requirements, motivation for learning, professional choices for future careers, outlooks on life. The research methods were the investigation based on questionnaire, the conversation and the systematic observation. The participants in the research were 200 students from two school levels: high school (students 15-19 years old) and faculty (students 19-30 years old). The data collected were processed using the SPSS analysis. The results of the research could be used to increase teachers’ awareness on their impact on students in their lifelong development.